Determination of Critical Level of Brassinosteroid (24-epibrassinoloid) for Heat-tolerance in Okra (Abelmoschus esculentus L.): Brassinosteroid-induced Heat-tolerance in Okra - Muhammad Wajid Khan; Muhammad Adnan Shahid; Rashad Mukhtar Balal (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
This study aimed at determining suitable dose of 24-epibrassinoloid (24-EBL) for improving morphological, physiological, and photochemical efficiency of PS II (Fv/Fm) characteristics in thermotolerant (Sabaz pari and Green wonder) and thermo-sensitive (MF-03 and Click-5769) genotypes of okra (Abelmoschus esculentus L.). The study was performed in a growth chamber at 40 °C by applying different levels of 24-EBL (i.e., 0 µM (control treatment), 0.25 µM, 0.50 µM, 0.75 µM, 1.00 µM, 1.25 µM and 1.50 µM). Foliar application of 24-EBL improved root and shoot growth, plant fresh and dry weight, leaf area, photosynthesis rate, chlorophyll content and photochemical efficiency of PS II in thermo-tolerant as well as of thermo-sensitive okra cultivars as compared to control plants. However, increase in the above stated characteristics was greater in thermo-tolerant okra genotypes as compared to thermos-sensitive genotypes, at all tested levels of 24-EBL. Greater reduction in electrolyte leakage in both thermo-sensitive and thermo-tolerant okra genotypes was observed with 1.50 µM 24-EBL. Considering increase in plant growth and biomass, leaf area, chlorophyll content, photosynthesis rate, photochemical efficiency of PS II and reduction in electrolyte leakage, both in thermos-tolerant and thermo-sensitive okra genotypes, it was concluded that 1.50 µM 24-EBL was the most suited level of brassinosteroid to improve the thermo-tolerance potential of okra genotypes.